The experimental study of rear fender production using plastic injection molding with Moldex3D simulation - Pitjamit, Siwasit; Jewpanya, Parida; Nuangpirom, Pinit; Wongpoo, Kraisorn; Sriyab, Suwannee (Engineering and Applied Science Research, 2023)
In the automotive industry are currently getting more attention because of a significant rise in demand for plastic products, particularly in the automotive, aerospace, sports, and household markets. To produce elaborate shapes and complex geometries with good dimensional precision, manufacturers placed increased focus on plastic injection molding. Adopting various cutting-edge technologies, such as CAD/CAM/CAE, is crucial to meeting demand since they help us understand the injection molding process and manufacture high-quality products. This article focuses on the analysis of the rear fender for automotive products used in the injection molding process using the software Moldex3D. One of the various types of software used to simulate a component's model is Moldex3D. Software called Moldex3D is commonly referred to as computer-aided engineering (CAE). According to the material and technological factors utilized, determines the melt front time, and sprue pressure. Polypropylene (PP) material has been taken into consideration in current research. The qualities of plastic products are influenced by a variety of factors. According to the investigation, the most suitable gate position for a consistent flow of mold material has been suggested. The injection speed and injection pressure are factors that affect the melt front time, according to the multilevel factorial design. To generate the best quality product, the operational factors must be accurate. With a change in parameters, there are changes in the product. The quality of manufacturing products without defects such improper location of runner, flow marks, short shots, hesitation, over packing, and others are referred to as the optimal parameter.